Growth and Business Analysis of Pacific White Shrimp (Litopenaeus vannamei) at Pangandaran, West Java - Astiyani, Wahyu Puji; Sofian, Achmad; Novitasari, Erina; Prama, Ega Aditya; Akbarurrasyid, Muhammad; Sudinno, Dinno (Agrikan Jurnal Agribisnis Perikanan, 2024)
The purpose of this study was to determine the enlargement technique and feasibility analysis of the Pacific white shrimp (Litopenaeus vannamei ) enlargement in CV. Rido Sejahtera shrimp ponds. The white shrimp rearing technique used a semi-intensive system with a stocking density of 75.52 tails/m2 and a pond area of 4,154 m2. Technical analysis produced indicators of several growth factors. These factors are an average body weight, daily growth, biomass, size, survival weight and feed conversion ratio. Based on our results, the average body weight was measured to be 31,65 gram/tail while the average Daily Growth, was recorded at 0,14 gram/day,. Biomass was recorded to be 6.290 kg or 15,14 ton/ha while the size was measured to be 31,6. Our results also yield a 75% survival rate while the Feed Conversion Ratio was recorded to be at 1,39. Based on our finding from a one year financial analysis, we concluded that the product indicators of investment costs would be Rp.307.695.400. Production costs would be around Rp.507.271.347 while revenues are around Rp.1.083.800.300. Based on these findings we concluded that profits Rp. 576.078.953, BEP production volume 3.059 kg, BEP production prices Rp. 40.359, B /C ratio 1.13, and payback period 0.53 years .The results of the study based on financial analysis concluded that the Pacific white shrimp (Litopenaeus vannamei) enlargement financial was feasible to operated, because it was profitable and the B/C ratio value was >1.